Comparative Study of Topical Versus Peribulbar Anaesthesia in Phacoemulsification Cataract Surgery. - Srinivasan Gopalan (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Aim To compare and evaluate patients discomfort and complications during phacoemulsification and implantation of foldable intraocular lenses under topical and peribulbar anesthesia in cataract. Materials and methods In this comparative study a total of 200 patients who underwent phacoemulsification with intraocular lens (IOL) implantation were included. Patients were randomly assigned under Topical anaesthesia (group 1, n=100) and Peribulbar anaesthesia (group 2, n=100). Results Group 1 ,2% had no movements and 51% had no movements.14% of group 1 and 34% of group 2 patients exhibited slight movements .47% of group 1 and 14% of group 2 had moderate movements.37% of group 1 and 1% of group 2 exhibited full movements. Mean value of group 1:2.21, SD: 0.78 and mean value of group 2:0.69,SD:0.84. Conclusion Topical anaesthesia is an effective alternative to peribulbar anaesthesia for phacoemulsification reducing the risks associated with peribulbar injection.